Política, espaço e cultura: as ligações entre poder e religião - Paul Claval (Confins)
This text continues and deepens the studies on the spatial dimension of culture and especially religion. He examines the intersection of the spatial dimensions of power relations and between beliefs and practices of religious and ideological nature